Analysis of the Synergistic Effect of Endophytic Bacteria and Metabolites on Yield in Soybean Roots Under Biochar with Nitrogen Fertilization - Hui Liu; Wanyu Dou; Wenlong Zhang; Yutao Li; Guoxin Shi; Lifang Fu; Lihong Wang (Agronomy)
The appropriate application of nitrogen fertilizers and biochar to the soil is beneficial for soybean growth, and a combination of biochar and nitrogen can improve low-nitrogen fertilizer utilization efficiency. However, the effect of the combination of biochar and nitrogen fertilizer on soybean roots is still unclear. Therefore, in this study, we investigate the changes in endophytic bacterial communities and metabolites in soybean roots under different combinations of biochar and nitrogen fertilizer treatments by setting different fertilization levels and using high-throughput sequencing and non-targeted metabolomics techniques. The results showed that applying 20 t/ha of biochar and 180 kg/ha of nitrogen fertilizer (C2N1) resulted in the highest soybean yield. By studying the endophytic bacterial community in soybean roots, it was observed that the dominant phyla were Proteobacteria, Bacteroidota, and Actinobacteriota, and the dominant genera were Bradyrhizobium, Streptomyces, and Rhizobacter. Moreover, a metabolic pathway analysis revealed that glycosylphosphatidylinositol (GPI)-anchor biosynthesis was the most significant metabolic pathway in the C0N1 vs. C0N0 comparison group, and glycerophospholipid metabolism was the most significant metabolic pathway in the C2N1 vs. C1N1 comparison group; they were both associated with regulatory mechanisms such as plant growth promotion and nutrient cycling. Structural equation modeling indicates that both endophytic bacteria and metabolites have a significant positive impact on yield. Bradyrhizobium and Rhizobium are observable variables with significant positive effects on endophytic bacteria, while Phe-Thr and 7-allyloxycoumarin are observable variables with significant positive effects on metabolites. Endophytic bacteria not only have a direct impact on crop yield, but also indirectly affect crop yield through their effects on metabolites. This study has important scientific value and guiding significance for improving soybean yields.